Synthesis of M-Hexaferrites Material Based on Natural Iron Sand with Metal Co Doping Using the Coprecipitation Method - Susilawati Susilawati; Aris Doyan; Lalu Muliyadi (Postgraduate, University of Mataram, 2021)
The synthesis of M-hexaferrite with metal doping Co (BaFe12-3xCoxO19 ) based on natural iron sand at Ketapang beach in Pringgabaya Subdistrict, East Lombok using the coprecipitation method has been successful. The basic ingredients used in this study were natural iron sand and BariumCarbonate (BaCO3) powder, while the doping material used was Cobalt (II) Chloride Hexahydrate (CoCl2.6H2O) powder with a variety of mole fraction (X = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0). The solvent uses 37% hydrochloric acid (HCl), 25% NH4OH solution, and distilled water. The sample formed was then calcined at 200 0C, 400 0C, 600 0C, 800 0C and 1000 0C. The resulting sample shows that there is an effect of Co doping and calcination temperature in the formation of barium M-hexaferrite. The higher the mole fraction of Co doping ions and the calcination temperature, the darker the color of the powder produced.